"Becoming a somebody": mobility, patronage and reconfiguration of transactional sexual relationships in postcolonial Africa. Issue 1 (2nd January 2022) - Mushonga, Rufaro H.; Dzingirai, Vupenyu
Abstract : The article explores the many ways in which Zimbabwean women married to Nigerian migrant entrepreneurs in Harare reconfigure transactional sexual relationships to further their own ends. Drawing on postcolonial feminism and based on a qualitative ethnographic inquiry, the article highlights women's agency motivated by pursuit of an idealised lifestyle, and patronage as the guiding principle in these transactional sexual relationships. This encompasses exchanges of sexual, monetary and emotional favours. Beyond this, women are also subordinated to moral principles of accumulation and distribution to their kinship networks, serving long-term objectives of social reproduction. These transactional relationships are guided by complex interlinkages of mutual exchange and bonds where sex, love, money and obligations are inextricably linked to each other. The article destabilises and disrupts mainstream views of women as weak and powerless, views that work to subordinate women based on their position in society. It posits that scholars must take into consideration the obvious and subtle factors that coalesce to create positive outcomes for women in transactional sexual relationships across the migration spectrum. Defining and understanding these positive outcomes greatly enhances the theoretical grounding of migration and the individual experiences of women.